Evaluation of heat transfer parameters in packed beds with cocurrent downflow of liquid and gas - Mariani, Nestor Javier (2001)
The results of an experimental investigation on heat transfer from a packed bed with cocurrent gas-liquid downflow to the wall are presented and analyzed in this contribution. The measurements cover the range of operating variables corresponding to the so-called trickle regime in beds presenting aspect ratios (tube to particle diameter ratio) from 4.67 to 34.26. Water and air were employed as model fluids. The heat transfer process was first analyzed by means of a two-dimensional pseudohomogeneous plug-flow model with two parameters, the effective radial thermal conductivity (ker) and the wall heat transfer coefficient (hw). ker is well correlated with liquid and gas Reynolds numbers and particle diameter, except for the lowest experimental aspect ratio (4.67). Instead, a meaningful correlation of hw stands only for aspect ratios larger than 15. These results are analyzed and the evidence points out to sustain the hypothesis that the model fails at low aspect ratios because an apparent contact resistance (1/hw) can no longer accommodate the effects of significant fluid by passing and finite size of the near-wall region. The experimental set of data were also used to develop a correlation for the overall heat transfer coefficient (ht), which can be employed satisfactorily to predict heat transfer rates in the whole range of variables here investigated. © 2001 Elsevier Science Ltd. All rights reserved.